THE CORELATION BETWEEN THE LEVEL OF ANXIETY WITH BACK PAIN IN PREGNANT WOMEN - ratih Ratih Suryaman (Jurnal Ilmiah Wijaya, 2020)
The high maternal mortality rate and young infant mortality rate due to pregnancy complications, one of them is caused by maternal anxiety. Based on the results of Indonesia Demographic and Health Survey in 2017 obtained the maternal mortality rate reached 359/100,000 live births. This study aim to determine the relationship between the level of anxiety with back pain in pregnant women in the third trimester in midwife Srie Herawati’s clinic Gunung Batu Bogor in 2020. This type of research is analytic survey with cross sectional approach. The population in this study were 32 third trimester pregnant womens and sample in this study is the entire population in this study. The collection of data obtained from questionnaires and observations. Based on the results of the study, of the 32 respondents, 17 respondents (53.1%) experienced severe levels of anxiety and 14 respondents (43.8%) of them experienced severe back pain, as well as the results obtained statistical test = 0.014 which means there is a significant relationship between the level of anxiety with back pain in pregnant women at midwife Srie Herawati’s clinic Gunung Batu Bogor in 2020. The conclusions there are the relationship between the level of anxiety with back pain in pregnant women at midwife Srie Herawati’s clinic Gunung Batu Bogor in 2020.